Self-Regulated Learning, Grit, and Learning Motivation in Developing Learning Achievement: A Review - Anggraeni, Dina; Wardani, Dewi Kusuma; Noviani, Leny (Formosa Journal of Multidisciplinary Research, 2024)
This article discusses the internal factors that role student learning achievement, including self-regulated learning, Grit, and learning motivation. This scientific article aims to build a research hypothesis of the influence between variables that will be used in further research. This Literature Review article is written using a library research method sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this literature review article are 1) the role of self-regulated learning in improve learning achievement, 2) the role of Grit in improving learning achievement, and 3) the role of learning motivation in improving learning achievement.